เหมืองข้อความและการประยุกต์ใช้ - วงศ์วิไลสกุล วรรณวิภา (วารสารปัญญาภิวัฒน์, 2013)
บทคัดย่อ เหมืองข้อความ เป็นเทคนิคการค้นหาความรู้ใหม่จากข้อมูลประเภทข้อความที่มีปริมาณมากโดยอัตโนมัติ โดยการสกัดคำ ค้นหารูปแบบ และความสัมพันธ์ที่ซ่อนอยู่ในชุดข้อความเอกสาร เพื่อให้เกิดความหมายและสามารถนำมาใช้ประโยชน์ได้ โดยสถาปัตยกรรมระบบของเหมืองข้อความมีความคล้ายคลึงกับสถาปัตยกรรมระบบในการค้นหาความรู้ในฐานข้อมูลประเภทข้อความ ซึ่งประกอบด้วย ขั้นตอนการเตรียมข้อมูล ขั้นตอนการค้นหากฎความสัมพันธ์ และขั้นตอนการนำเสนอผลลัพธ์ที่ชัดเจน ส่วนประโยชน์ของเหมืองข้อความนั้น คือการทำให้สารสนเทศในรูปแบบข้อความสามารถเข้าถึง วิเคราะห์ และประมวลผลภายในเวลาอันรวดเร็ว โดยผู้ใช้สามารถเข้าใจและใช้ประโยชน์จากเอกสารที่จัดเก็บไว้เป็นจำนวนมากได้อย่างมีประสิทธิภาพ แนวทางสำคัญในการประยุกต์ใช้เหมืองข้อความ คือ การประยุกต์ใช้ตามหน้าที่ และตามกลุ่มการใช้งาน และขณะนี้ได้มีการพัฒนาเหมืองข้อความขึ้นเป็นเหมืองข้อความแสดงความคิดเห็น ซึ่งผสานเทคนิคของการสืบค้นข้อมูลเข้ากับการประมวลผลภาษาธรรมชาติ ทำให้สามารถสรุปความคิดเห็นที่หลากหลายบนเครือข่ายสังคมออนไลน์ให้เข้าใจง่ายยิ่งขึ้น คำสำคัญ : เหมืองข้อความ เหมืองข้อมูล การค้นหาความรู้ ฐานข้อมูลประเภทข้อความ Abstract Text Mining is a new technique of a search engine done by automatically going through large quantity of information. This is done by extracting an information, finding pattern, as well as hidden meaning and relation within the set documents. This makes it meaningful and very beneficial. The system architecture of text mining is similar to the one of Knowledge Discovery in Textual databases. This is including Text Preprocessing phase, Association Rule Mining phase and Visualization phase. The benefit of text mining is to help improve information technology in the form of text to be easier accessible in an analytical way. The users will be able to understand and benefit from this efficiently. This will be done with the use of large number of collected documents. The main approach to text mining is to apply it according to function and usability. Nowadays, text mining has been developed into an opinion mining. This combines the mean of retrieving information with Natural Language Processing (NLP). Therefore, this will be easier especially with different opinion from an online social network. Keywords : Text Mining, Data Mining, Knowledge Discovery, Textual databases